HOW BOARD SIZE MODERATES THE EFFECT OF CEO POWER ON ESG - Hesniati, Hesniati; Jeffrey, Jeffrey; Candra, Tony (LPPM STIE Muhammadiah Bandung, 2025)
This study aims to explore how CEO Power affects ESG with the moderating role of board size which the answer is remains unexplored, while in the extant literature the impact of ESG is the most discussed. The findings was conducted on public companies listed on the Indonesia Stock Exchange (IDX) reveal that the direct impact of CEO Power on ESG performance is significant. However,the result of the moderating effect of Board Size does not show a significant effect. The findings of this study contributes by revealing how CEO Power affects ESG with the moderating role of Board Size.